A low-complexity method for the design of low-delay cosine-modulated filter banks - Wu, Changzhi (2010)
We present a new method for the design of the cosine-modulated filter bank with low complexity and low delay. The design of such a filter bank is formulated as a nonconvex optimization problem with equality constraints. An iterative scheme is developed to solve this optimization problem. To illustrate the effectiveness of the proposed method, a numerical example is presented. Comparing our method with that in [14], our approach can reduce the number of filter taps by up to 40 % while maintaining a relatively low delay. © 2010 IEEE.